Chad - The Safe Motherhood Project : Strengthening the Health System - World Bank (Washington, DC, 2012)
In this largely Muslim population, only about a third of women have any schooling, most marry young (nearly 80 percent by the age of 19) and by the age of 18, more than half have had their first child. Nearly 1 in every 5 women joins in a polygamous marriage. As both women and men state they want 8 and 16 children, respectively, the use of modern contraception remains strikingly low at 1 percent among women and fertility is high. The objectives of this project are to: (a) enhance capability at the central level to support regional health services (16 percent); (b) ensure accessibility of the population to low-cost essential drugs (21 percent); and (c) improve access to basic health services in the regions of Guera and Tandjile (63 percent). While the scope of (a) and (b) are nationwide and support capacity building for health generally, (c) targets two regions for the implementation of these efforts with an emphasis on Safe Motherhood. This project builds on a prior Bank project that included support for the general health sector, the Social Development Action Project (PADS). To further support the nationwide health efforts, and specifically the newly-adopted National Drug Policy (NDP), the Bank assists to ensure overall geographical as well as financial accessibility of the population to essential generic drugs as a prerequisite to the successful implementation of cost-recovery. The NDP selects drugs essential for dealing effectively with at least 90 percent of the curative and prophylactic needs of the majority of the population, including the major complications that kill women.